To Compare the Recurrence Rate of Suture Repair V/S Mesh Repair In Incisional Hernia: An Hospital Based Prospective Study. - Shankar Singh Gaur; Sandeep Agarwal (Asian Journal of Medical Research, 2019)
Background: The technique of hernia repair is usually based on custom rather than evidence. The aim of this study to compare the recurrence rate of suture repair v/s mesh repair in incisional hernia. Subjects and Methods:A Prospective Clinical Hospital Based Study done on 30 patients in Department of Surgery, P.D.U. Medical College& Hospitals, Churu (Rajasthan) during one year period. Patients were randomly assigned to undergo suture repair or mesh repair. Follow-up of cases was done after 6 months after surgery on an outpatient basis for recurrence of hernia. Results:Our results showed that small (0-5cm) gap size 86.66% cases. Most common post-operative complication was 26.66% chest infection, followed by 20% wound infection in group A and fever was present 20% in group B. The recurrence of hernia was present in 26.66% cases in group A and 6.66% in group B. It was statistically significant (P=0.0488*).Conclusion: We concluded that in small defect incisional hernias, mesh repair provides better results than suture repair modalities.